Dominant 5P Marketing Mix Elements Influencing Umrah Pilgrims’ Interest - Mujahidah Nabilah Taufiqoh; Yetty Faridatul Ulfah; Muhammad Fathurrahman (Indonesian Journal of Da'wah Management Scholars, 2026)
Purpose – This study aims to examine the partial and simultaneous effects of the 5P marketing mix elements—product, price, place, promotion, and people—on Umrah pilgrims’ interest in selecting travel services at PT. Hajar Aswad Mubaroq Surakarta. It also seeks to identify the most dominant variable influencing pilgrims’ interest. Design/methodology/approach – This research employed a quantitative approach, with data collected from 90 respondents through structured questionnaires. The data were analysed by using statistical techniques, including t-tests to assess partial effects, F-tests to evaluate simultaneous effects, and the coefficient of determination (R²) to measure explanatory power. Findings – The results indicate that all five marketing mix elements significantly influence pilgrims’ interest both partially and simultaneously. The F-test result shows a value of 22.092, with an R² of 54.2%, indicating that the model explains a substantial proportion of variance in pilgrims’ interest. Among the variables, place is identified as the most dominant factor, followed by people, product, price, and promotion. Research implications – These findings underscore the strategic importance of optimizing all elements of the 5P marketing mix, particularly place and people. Travel agencies are encouraged to enhance accessibility and strategic location, as well as improve the competence and service quality of human resources, in order to strengthen pilgrims’ interest and competitiveness in the Umrah travel market. Originality/value – This study contributes to the Umrah travel marketing literature by comprehensively examining the simultaneous and partial effects of the 5P marketing mix on pilgrims’ interest in selecting Hajj and Umrah travel services, while identifying place as the most influential factor shaping customer interest.